Public health nurses’ practices to promote work–family balance in maternal and child health services in Japan: a qualitative descriptive study - Yuko Shimoda; Miyuki Ishii (BMC Public Health, 2026)
Abstract Background Work–family balance (WFB), defined as the capacity to engage meaningfully in both professional and familial roles, is an escalating global public health concern. While municipal public health nurses (PHNs) in Japan are expected to support dual-earner families through universal maternal and child health (MCH) services, their professional reasoning and specific intervention strategies remain underexplored. In this study, we aimed to investigate WFB-related consultations and the specific support provided by PHNs, with the primary aim of delineating overall PHN support strategies. Methods We used a qualitative descriptive approach within a naturalistic inquiry framework. Semi-structured interviews were conducted with ten municipal PHNs involved in MCH services in a suburban region of Japan. The data were analyzed thematically to identify consultation patterns and professional support strategies related to WFB. Results Parents’ consultations were characterized by four themes, revealing that PHNs interpret immediate parenting “troubles” as manifestations of structural WFB conflicts. PHN support strategies were synthesized into seven interrelated domains: (1) assessing latent WFB needs beyond explicit requests, (2) navigating daycare resources and administrative enrollment procedures, (3) supporting balanced and shared decision-making, (4) offering child-development–centered guidance, (5) providing timing-sensitive anticipatory guidance, (6) facilitating role rebalancing and paternal involvement, and (7) coordinating multi-sectoral “traffic-control.” Collectively, these practices constitute a “strategic navigation” process in which PHNs utilize universal MCH platforms to proactively mitigate work–family conflicts. Conclusions PHNs act as essential navigators and “traffic-controllers,” balancing parental employment needs with child developmental well-being. This role is grounded in a relational stance of psychosocial support that enables more instrumental forms of guidance. By leveraging Japan’s unique universal MCH infrastructure, PHNs transform individual role conflicts into public health priorities. Accordingly, this case offers empirically grounded insights that may inform the integration of WFB support into routine community health systems in other high-income countries, contributing to broader discussions on parental well-being and gender equity.